Silicon-carbon negative electrode material and preparation method thereof

By introducing boron elements into silicon carbon anode material and adopting gaseous deposition technology, the problem of insufficient conductivity and rate performance of the material is solved, efficient electron transfer and stable carbonization layer are achieved, and material costs are reduced.

CN119822356APending Publication Date: 2025-04-15JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 0 Cites 7 Cited by

Patent Information

Application Number
CN202510026892.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing vapor-deposited silicon carbon anode material is easily damaged during the circulation process, and its conductivity is poor, which affects the rate performance. At the same time, the carbonization rate is low during the preparation of porous carbon, resulting in high material cost.

Method used

By introducing boron elements, a conductive network is formed to increase the electron concentration and transfer rate; silicon deposition and carbon coating are used for gaseous silicon sources and carbon sources to improve the conductive and rate performance of the material; at the same time, the residual carbon rate and thermal cracking temperature of porous carbon are improved through the activation and carbonization process.

Benefits of technology

The conductive performance and rate performance of silicon carbon anode material are significantly improved, the material cost is reduced, and the stability of the carbonized layer is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005234287260000091
    Figure BDA0005234287260000091
  • Figure BDA0005234287260000101
    Figure BDA0005234287260000101
Patent Text Reader

Abstract

The invention provides a silicon-carbon negative electrode material and a preparation method thereof. The preparation method comprises the following steps: a) mixing a phenol monomer, an aldehyde solution, ammonia water and water, dropwise adding a boric acid solution for reaction, and curing to obtain boron-containing phenolic resin; b) carbonizing the boron-containing phenolic resin obtained in the step a), mixing with alkali, and activating to obtain boron-doped porous carbon; and c) carrying out silicon deposition on the boron-doped porous carbon obtained in the step b) by adopting a gaseous silicon source, carrying out carbon coating by adopting a gaseous carbon source, and cooling to obtain the silicon-carbon negative electrode material. Compared with the prior art, the preparation method provided by the invention has the advantages that a conductive network can be formed by doping the boron element, the electron concentration can be improved, the electron transfer rate is favorably improved, the conductivity of the material is effectively enhanced, and the rate capability of the negative electrode material is effectively improved; meanwhile, the residual carbon rate in the porous carbon preparation process can be greatly increased, and the cost of the whole silicon-carbon negative electrode material is effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative electrode materials, and more specifically, to a silicon-carbon negative electrode material and a preparation method thereof. Background Art

[0002] The vapor-deposited silicon-carbon negative electrode uses porous carbon as a substrate and the principle of silane cracking, deposition and adsorption of nano-silicon. This structure can effectively limit the expansion of silicon and is one of the most promising silicon-carbon materials of the new generation. Since the vapor-deposited silicon-carbon negative electrode will be coated with a layer of carbon during the preparation process, but the carbon layer is often relatively thin, usually around tens of nanometers, it is easily destroyed during the cycle process. In addition, since it is usually coated at a low temperature, the conductivity of the carbon layer is often poor, thus affecting the rate performance of the material. In addition, during the preparation process of porous carbon, due to the low carbonization rate of its precursor, only 40% to 50%, the porous carbon is expensive, and the overall price of the silicon-carbon negative electrode is also high. Summary of the invention

[0003] In view of this, the object of the present invention is to provide a silicon-carbon negative electrode material and a preparation method thereof. The preparation method provided by the present invention has a simple process, strong feasibility and low cost; the prepared product has good rate performance on the basis of good and stable performance.

[0004] The present invention provides a method for preparing a silicon-carbon negative electrode material, comprising the following steps:

[0005] a) mixing a phenol monomer, an aldehyde solution, aqueous ammonia and water, adding a boric acid solution dropwise to react, and obtaining a boron-containing phenolic resin after curing;

[0006] b) carbonizing the boron-containing phenolic resin obtained in step a), mixing it with a base, and activating it to obtain boron-doped porous carbon;

[0007] c) using a gaseous silicon source to deposit silicon on the boron-doped porous carbon obtained in step b), then using a gaseous carbon source to perform carbon coating, and obtaining a silicon-carbon negative electrode material after cooling.

[0008] Preferably, the phenol monomer in step a) is selected from one or more of phenol, m-phenol, and boric acid phenyl ester;

[0009] The aldehyde solution is selected from one or more of formaldehyde solution, acetaldehyde solution, furfural solution and paraformaldehyde solution;

[0010] The phenol-aldehyde molar ratio of the phenol monomer to the aldehyde solution is 1:(1-2).

[0011] Preferably, the mixing method in step a) is stirring; the stirring speed is 50 r / min to 250 r / min, the temperature is 50° C. to 90° C., and the time is 2 h to 3 h.

[0012] Preferably, the mass ratio of the boric acid solution added dropwise in step a) is 1% to 10%;

[0013] The reaction temperature is 50° C. to 90° C., the stirring speed is 50 r / min to 250 r / min, and the stirring time is 1 h to 3 h.

[0014] Preferably, the curing temperature in step a) is 100° C. to 180° C., and the curing time is 20 h to 36 h.

[0015] Preferably, the carbonization process in step b) is specifically as follows:

[0016] The boron-containing phenolic resin is placed in a tubular furnace, and the nitrogen flow rate is set to 0.5L / min to 2L / min for evacuation for 1h to 2h, and then the nitrogen flow rate is reduced to 0.1L / min to 0.5L / min, and the temperature is increased to 700°C to 1000°C at a heating rate of 2°C / min to 5°C / min, and carbonized for 1h to 3h. After natural cooling, boron-doped carbon is obtained.

[0017] Preferably, the activation process in step b) is specifically as follows:

[0018] The carbonized boron-containing phenolic resin is mixed with an alkali in an alkali-carbon ratio of 1: (1-4), placed in a nickel crucible and placed in a tubular furnace, the nitrogen flow rate is set to 0.5L / min-2L / min, emptied for 1h-3h, then the nitrogen flow rate is reduced to 0.1L / min-0.5L / min, the temperature is increased to 350℃-450℃ at a heating rate of 2℃ / min-5℃ / min, kept warm for 0.5h-2h, then heated to 700℃-900℃ at a heating rate of 5℃ / min-10℃ / min, activated for 0.5h-2h, and naturally cooled and crushed by air flow to obtain boron-doped porous carbon.

[0019] Preferably, the gaseous silicon source in step c) is selected from one or more of monosilane, disilane, monochlorotrihydrosilane, dichlorosilane, trisilane, trichlorosilane and silicon chloride;

[0020] The silicon deposition process is specifically as follows:

[0021] The boron-doped porous carbon is placed in a rotary furnace, and the nitrogen flow rate is set to 1L / min~5L / min for 1h~3h, and the nitrogen flow rate is reduced to 0.5L / min~1L / min, and then the temperature is increased to 300℃~600℃ at a heating rate of 2℃ / min~5℃ / min, and a gaseous silicon source is introduced, and the flow rate ratio of the gaseous silicon source to nitrogen is (2~4):1. Silicon deposition is carried out by chemical vapor deposition for 6h~10h to complete the silicon deposition process.

[0022] Preferably, the gaseous carbon source in step c) is selected from one or more of acetylene, methane, ethane and ethylene;

[0023] The process of carbon coating using a gaseous carbon source is specifically as follows:

[0024] After silicon deposition is completed, the valve of the gaseous silicon source is closed, the nitrogen flow rate remains unchanged, and a gaseous carbon source is introduced at a flow rate of 0.5L / min to 1L / min. Vapor deposition is performed for 1h to 3h to obtain a boron-doped silicon-carbon negative electrode material.

[0025] The present invention also provides a silicon-carbon negative electrode material, which is prepared by the preparation method described in the above technical solution.

[0026] The invention provides a silicon-carbon negative electrode material and a preparation method thereof; the preparation method comprises the following steps: a) mixing a phenol monomer, an aldehyde solution, ammonia water and water, dripping a boric acid solution to react, and obtaining a boron-containing phenolic resin after solidification; b) carbonizing the boron-containing phenolic resin obtained in step a), mixing it with an alkali, and activating it to obtain a boron-doped porous carbon; c) using a gaseous silicon source to deposit silicon on the boron-doped porous carbon obtained in step b), and then using a gaseous carbon source to perform carbon coating, and cooling it to obtain the silicon-carbon negative electrode material. Compared with the prior art, the preparation method provided by the present invention can form a conductive network through the doping of boron elements, which can increase the electron concentration, is beneficial to increase the electron transfer rate, effectively enhance the conductivity of the material, and effectively improve the rate performance of the negative electrode material; at the same time, the doped boron element greatly increases the residual carbon rate of the material during the carbonization process, because a three-dimensional network structure containing boron is formed during the polymerization process, which significantly increases the thermal cracking temperature of the material, thereby reducing the generation of volatile carbon oxides such as CO2 during the resin curing carbonization process, thereby enhancing the stability of the carbonized layer; in addition, the introduction of boron into PF can also increase the graphitization degree and crystallinity of the carbon layer, so that BPF forms a more ordered and compact carbon structure during the thermal decomposition process, reducing the defects of the carbon layer microstructure, which is beneficial to improving its residual carbon rate and material conductivity, and can increase the residual carbon rate in the porous carbon preparation process from 50% to more than 75%, effectively reducing the cost of the entire silicon-carbon negative electrode material.

[0027] At the same time, the preparation method provided by the present invention has simple process, easy operation, mild conditions, easy control, high feasibility, and broad application prospects. DETAILED DESCRIPTION

[0028] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] The present invention provides a method for preparing a silicon-carbon negative electrode material, comprising the following steps:

[0030] a) mixing a phenol monomer, an aldehyde solution, aqueous ammonia and water, adding a boric acid solution dropwise to react, and obtaining a boron-containing phenolic resin after curing;

[0031] b) carbonizing the boron-containing phenolic resin obtained in step a), mixing it with a base, and activating it to obtain boron-doped porous carbon;

[0032] c) using a gaseous silicon source to deposit silicon on the boron-doped porous carbon obtained in step b), then using a gaseous carbon source to perform carbon coating, and obtaining a silicon-carbon negative electrode material after cooling.

[0033] The present invention provides a method for preparing a low-cost, high-rate vapor-deposited silicon-carbon negative electrode, wherein a boron compound is introduced during the preparation of a resin precursor, and a three-dimensional network structure containing the boron element is formed by chemical crosslinking copolymerization, and a high-carbon residual amount, boron-doped porous carbon is obtained by carbonization activation, and then a low-cost, high-rate silicon-carbon negative electrode is obtained by chemical vapor deposition of silicon nanoparticles and carbon coating process.

[0034] The invention firstly mixes phenol monomer, aldehyde solution, ammonia water and water, then drops boric acid solution to react, and obtains boron-containing phenolic resin after curing.

[0035] In the present invention, the phenol monomer is used for the synthesis of phenolic resin, and is preferably selected from one or more of phenol, m-phenol, and boric acid phenyl ester, and more preferably phenol; the present invention has no special restriction on the source of the phenol monomer, and commercially available products well known to those skilled in the art can be used.

[0036] In the present invention, the aldehyde solution is also used for the synthesis of phenolic resin, and is preferably selected from one or more of formaldehyde solution, acetaldehyde solution, furfural solution, and paraformaldehyde solution, and more preferably formaldehyde solution; the present invention has no special restrictions on the source of the aldehyde solution, and commercially available products well known to those skilled in the art can be used.

[0037] In the present invention, the phenolic monomer and aldehyde solution have a phenolic aldehyde molar ratio of preferably 1: (1-2), more preferably 1: (1.1-1.8). In the present invention, if the phenolic aldehyde molar ratio is less than 1, the molecular weight is too low, which is not conducive to subsequent cross-linking and curing, while if the phenolic aldehyde molar ratio is greater than 2, it is easy to react violently to form a block, or the particle size distribution is uneven.

[0038] The present invention has no special limitation on the source of the aqueous ammonia, and commercially available products known to those skilled in the art may be used; the water is preferably deionized water known to those skilled in the art.

[0039] In a preferred embodiment of the present invention, the dosage ratio of the phenol monomer, aldehyde solution, ammonia water and water is preferably (0.5kg-2kg): (0.8kg-3.6kg): (100mL-360mL): (10L-20L), and more preferably (0.7kg-2kg): (0.9kg-3.6kg): (120mL-360mL): (10L-18L). In the present invention, the mass range of the phenol monomer and the aldehyde solution is limited to the above-mentioned phenol-aldehyde molar ratio, while ammonia water <100mL has a low reaction rate and a too low molecular weight, which is not conducive to the subsequent cross-linking and curing, and >360mL has a violent reaction and agglomerates, and the particle size distribution is uneven.

[0040] The present invention has no special limitation on the mixing device, and a stainless steel reactor well known to those skilled in the art can be used; the mixing method is preferably stirring; the stirring speed is preferably 50 r / min to 250 r / min, more preferably 100 r / min to 200 r / min, the temperature is preferably 50°C to 90°C, more preferably 60°C to 70°C, and the time is preferably 2h to 3h, more preferably 2.5h.

[0041] The present invention has no particular limitation on the source of the boric acid solution, and commercially available products known to those skilled in the art may be used.

[0042] In the present invention, the mass ratio of the boric acid solution added dropwise is preferably 1% to 10%, more preferably 2% to 8%. In the present invention, a mass ratio of the boric acid solution added dropwise < 2% will result in insufficient boron doping and no significant improvement in rate performance, and a mass ratio of > 8% will result in a large amount of unreacted boric acid and increase costs.

[0043] In the present invention, the reaction temperature is preferably 50°C to 90°C, more preferably 60°C to 70°C, the stirring speed is preferably 50r / min to 250r / min, more preferably 100r / min to 200r / min, and the stirring time is preferably 1h to 3h, more preferably 1h; the phenolic resin is obtained, and then placed in a sagger and placed in a box furnace for curing. In the present invention, the temperature of the above reaction is lower than 50°C, and the molecular weight is too low, which is not conducive to the subsequent cross-linking and curing. A water system is used for polymerization, and the reaction temperature is higher than 90°C, the reaction exotherm is aggravated, and it is easy to boil and cause implosion; the stirring speed is limited to the above range to ensure good uniformity of the solution; the stirring time is <1h, the molecular weight is too low, which is not conducive to the subsequent cross-linking and curing, and the stirring time is too long, which is easy to cause excessive particles to form agglomerates.

[0044] In the present invention, the curing temperature is preferably 100°C to 180°C, more preferably 110°C to 120°C, and the curing time is preferably 20h to 36h, more preferably 24h to 30h. In the present invention, the curing temperature and time are similarly, if it is lower than the lower limit of the above range, the curing is incomplete, the resin crosslinking degree is low, the strength is poor, and the carbonization rate is low; if it is higher than the upper limit of the above range, the curing is complete, which will increase energy consumption.

[0045] After obtaining the boron-containing phenolic resin, the present invention carbonizes the obtained boron-containing phenolic resin, mixes it with an alkali, and activates it to obtain boron-doped porous carbon.

[0046] In the present invention, the carbonization process is preferably specifically as follows:

[0047] The boron-containing phenolic resin is placed in a tubular furnace, and the nitrogen flow rate is set to 0.5L / min to 2L / min for evacuation for 1h to 2h, and then the nitrogen flow rate is reduced to 0.1L / min to 0.5L / min, and the temperature is increased to 700°C to 1000°C at a heating rate of 2°C / min to 5°C / min, and carbonized for 1h to 3h. After natural cooling, boron-doped carbon is obtained.

[0048] In the present invention, the alkali is preferably potassium hydroxide powder and / or sodium hydroxide powder, more preferably potassium hydroxide powder; commercially available products well known to those skilled in the art may be used.

[0049] In the present invention, the activation process is preferably specifically as follows:

[0050] The carbonized boron-containing phenolic resin is mixed with alkali in an alkali-carbon ratio of 1: (1-4), preferably 1: 2, and then placed in a nickel crucible and placed in a tubular furnace. The nitrogen flow rate is set to 0.5L / min-2L / min and emptied for 1h-3h, then the nitrogen flow rate is reduced to 0.1L / min-0.5L / min, and the temperature is increased to 350℃-450℃ at a heating rate of 2℃ / min-5℃ / min, and kept warm for 0.5h-2h, and then the temperature is increased to 700℃-900℃ at a heating rate of 5℃ / min-10℃ / min, and activated for 0.5h-2h. After natural cooling, the carbon is crushed by air flow to obtain boron-doped porous carbon. In the present invention, if the alkali-carbon ratio is too low, the degree of activation pore formation will be too low, and the total pore volume <0.5cm 3 / g, it is impossible to deposit enough silicon and obtain the appropriate capacity; if the alkali-carbon ratio is too high, the activation reaction will be too violent, a large number of macropores will be formed, silicon cannot be deposited, and the yield will be very low and the cost will increase; the nitrogen flow rate is the same as above, while the heating rate and temperature range are limited to ensure the activation effect.

[0051] In the present invention, when the porous carbon is doped with boron, a conductive network can be formed, which can increase the electron concentration, which is beneficial to increase the electron transfer rate and effectively enhance the conductivity of the material, so that the negative electrode material exhibits good rate performance; in addition, the preparation of a precursor with a high residual carbon rate can effectively reduce the cost of the overall porous carbon.

[0052] After obtaining the boron-doped porous carbon, the present invention uses a gaseous silicon source to perform silicon deposition on the obtained boron-doped porous carbon, then uses a gaseous carbon source to perform carbon coating, and obtains a silicon-carbon negative electrode material after cooling.

[0053] In the present invention, the gaseous silicon source is preferably selected from one or more of monosilane, disilane, monochlorotrihydrosilane, dichlorosilane, trisilane, trichlorosilane, and silicon chloride, and is more preferably monosilane (SiH4); the present invention has no special restrictions on the source of the gaseous silicon source, and commercially available products familiar to those skilled in the art can be used.

[0054] In the present invention, the process of silicon deposition is preferably as follows:

[0055] The boron-doped porous carbon is placed in a rotary furnace, and the nitrogen flow rate is set to 1L / min~5L / min for 1h~3h, and the nitrogen flow rate is reduced to 0.5L / min~1L / min, and then the temperature is increased to 300℃~600℃, preferably 380℃~485℃, at a heating rate of 2℃ / min~5℃ / min. A gaseous silicon source is introduced, and the flow rate ratio of the gaseous silicon source to nitrogen is (2~4):1, preferably 3:1. Silicon deposition is carried out by chemical vapor deposition for 6h~10h to complete the silicon deposition process.

[0056] In the present invention, the gaseous carbon source is preferably selected from one or more of acetylene, methane, ethane, and ethylene, and more preferably acetylene; the present invention has no special limitation on the source of the gaseous carbon source, and commercially available products known to those skilled in the art can be used.

[0057] In the present invention, the process of carbon coating using a gaseous carbon source is preferably as follows:

[0058] After silicon deposition is completed, the valve of the gaseous silicon source is closed, the nitrogen flow rate remains unchanged, and a gaseous carbon source with a flow rate of 0.5L / min to 1L / min is introduced. Carbon coating is carried out by chemical vapor deposition for 1h to 3h to obtain a boron-doped silicon-carbon negative electrode material; finally, the material is cooled and discharged after natural cooling to obtain a low-cost, high-rate boron-doped silicon-carbon negative electrode material.

[0059] The present invention also provides a silicon-carbon negative electrode material, which is prepared by the preparation method described in the above technical solution. In the present invention, the structure of the silicon-carbon negative electrode material is a structure in which silicon particles are dispersed in boron-doped porous carbon particles.

[0060] The invention provides a silicon-carbon negative electrode material and a preparation method thereof; the preparation method comprises the following steps: a) mixing a phenol monomer, an aldehyde solution, ammonia water and water, dripping a boric acid solution to react, and obtaining a boron-containing phenolic resin after solidification; b) carbonizing the boron-containing phenolic resin obtained in step a), mixing it with an alkali, and activating it to obtain a boron-doped porous carbon; c) using a gaseous silicon source to deposit silicon on the boron-doped porous carbon obtained in step b), and then using a gaseous carbon source to perform carbon coating, and cooling it to obtain the silicon-carbon negative electrode material. Compared with the prior art, the preparation method provided by the present invention can form a conductive network through the doping of boron elements, which can increase the electron concentration, is beneficial to increase the electron transfer rate, effectively enhance the conductivity of the material, and effectively improve the rate performance of the negative electrode material; at the same time, the doped boron element greatly increases the residual carbon rate of the material during the carbonization process, because a three-dimensional network structure containing boron is formed during the polymerization process, which significantly increases the thermal cracking temperature of the material, thereby reducing the generation of volatile carbon oxides such as CO2 during the resin curing carbonization process, thereby enhancing the stability of the carbonized layer; in addition, the introduction of boron into PF can also increase the graphitization degree and crystallinity of the carbon layer, so that BPF forms a more ordered and compact carbon structure during the thermal decomposition process, reducing the defects of the carbon layer microstructure, which is beneficial to improving its residual carbon rate and material conductivity, and can increase the residual carbon rate in the porous carbon preparation process from 50% to more than 75%, effectively reducing the cost of the entire silicon-carbon negative electrode material.

[0061] At the same time, the preparation method provided by the present invention has simple process, easy operation, mild conditions, easy control, high feasibility, and broad application prospects.

[0062] In order to further illustrate the present invention, the following examples are provided for detailed description. The raw materials used in the following examples of the present invention are all commercially available.

[0063] Example 1

[0064] Step 1: Add 0.7kg phenol, 0.9kg formaldehyde solution (phenol-formaldehyde molar ratio is 1:1.5), 120mL ammonia water, and 18L water into a 30L stainless steel reactor, start stirring, the stirring speed is 200r / min, the temperature is set to 60℃, after stirring for 2.5h, add 2% boric acid solution and stir for 1h to obtain phenolic resin. Put the obtained resin into a sagger and cure it at 110℃ for 24h to obtain boron-containing phenolic resin.

[0065] Step 2: Place the above resin sample in a tubular furnace, set the nitrogen flow rate to 0.5L / min to empty for 2h, then reduce the nitrogen flow rate to 0.1L / min, heat to 800℃ at a heating rate of 2℃ / min, carbonize for 3h, and cool naturally to obtain boron-doped carbon. The above boron-doped carbon and KOH powder are mixed evenly according to the alkali-carbon ratio (mass ratio) of 1:2 and placed in a nickel crucible, and then placed in a tubular furnace, set the nitrogen flow rate to 0.5L / min to empty for 2h, then reduce the nitrogen flow rate to 0.1L / min, heat to 350℃ at a heating rate of 2℃ / min, keep warm for 30 minutes, then heat to 800℃ at a heating rate of 10℃ / min, and activate for 1h. After cooling naturally, use air flow pulverization to obtain boron-doped porous carbon with suitable particle size (6-10μm).

[0066] Step 3: Take a certain mass (1kg) of porous carbon and place it in a rotary furnace. Set the nitrogen flow rate to 5L / min and drain for 2h, reduce the nitrogen flow rate to 1L / min, then raise the temperature to 450℃ at 5℃ / min, introduce monosilane (SiH4), and use chemical vapor deposition to deposit silicon, wherein the flow rate ratio of monosilane to nitrogen is 3:1, and the vapor deposition is performed for 8h; after the silicon deposition is completed, close the monosilane valve, keep the nitrogen flow rate unchanged, and introduce acetylene at a flow rate of 1L / min, and vapor deposition is performed for 2h. Then cool naturally, cool the material and obtain a boron-doped silicon-carbon negative electrode material.

[0067] Example 2

[0068] The preparation method provided in Example 1 is adopted, except that the mass ratio of boric acid added in step 1 is 4%.

[0069] Example 3

[0070] The preparation method provided in Example 1 is adopted, except that the mass ratio of boric acid added in step 1 is 8%.

[0071] Example 4

[0072] The preparation method provided in Example 1 is adopted, except that the molar ratio of phenolic acid in step 1 is 1:1.1.

[0073] Example 5

[0074] The preparation method provided in Example 1 is adopted, except that the molar ratio of phenolic acid in step 1 is 1:1.8.

[0075] Comparative Example 1

[0076] The preparation method provided in Example 1 is adopted, except that the mass ratio of boric acid added in step 1 is 0%.

[0077] Test Characterization:

[0078] 1) The boron content of the spherical silicon-carbon negative electrode in each embodiment and comparative example was tested using an EA element analyzer.

[0079] 2) The residual carbon rate was tested by a thermal gravimetric analyzer (TGA), with the parameters ranging from room temperature to 1000°C, a heating rate of 5°C / min, and a nitrogen atmosphere.

[0080] 3) The electrical conductivity of the spherical silicon-carbon negative electrode in each embodiment and comparative example was tested using an intelligent powder resistivity tester at a test pressure of 2 to 30 MPa.

[0081] Preparation of the battery:

[0082] The negative electrode sheet is composed of 94% active material mixed with gas phase silicon carbon and graphite (the mixing ratio of gas phase silicon carbon is 10%), 1.5% carbon black conductive agent, 0.05% carbon nanotubes, and 5% sodium carboxymethyl cellulose; the preparation process is: the active material, conductive agent and binder are added with deionized water and stirred, the viscosity is adjusted, and the negative electrode slurry is obtained, which is coated on at least one side of the negative electrode copper foil collector, dried, and pressed to obtain a 100μm thick silicon negative electrode sheet. The positive electrode sheet is composed of 97% high nickel ternary positive electrode material (NMC622, chemical formula LiNi 0.6 Mn 0.2 Co 0.2 O), 2% carbon black conductive agent, 0.08% CNT, 1% PVDF binder, the preparation process is: active material, conductive agent, binder plus solvent NMP, stirring, adjusting viscosity, obtaining positive electrode slurry, coating on at least one side of the positive and negative sides of the positive electrode aluminum foil collector, drying, and pressing to obtain a positive electrode sheet.

[0083] The silicon negative electrode sheet, the separator and the positive electrode sheet are wound to obtain a battery cell, and the battery cell is filled with a battery shell, dried, injected with electrolyte, packaged, formed and divided into different capacities to obtain a lithium-ion battery.

[0084] Test the rate performance of the battery cell, the specific steps are: 1) stand at (25±2)℃ for 5 minutes; 2) 1C constant current discharge, cut-off voltage 2.5V; 3) stand for 30min; 4) 1C constant current charge, cut-off voltage 4.25V, and then constant voltage charge to current ≤0.05C; 5) stand for 30min; 6) XC constant current discharge to cut-off voltage 2.5V; 7) repeat 3) to 6) to obtain the discharge capacity of different rate batteries. X is 2C, 3C, 5C.

[0085] The test results are shown in Tables 1-2 below.

[0086] Table 1

[0087]

[0088]

[0089] Table 2

[0090] serial number 2C capacity retention rate (%) 3C capacity retention rate (%) 5C capacity retention rate (%) Example 1 98.25 95.48 78.25 Example 2 98.55 96.25 82.54 Example 3 99.12 97.13 87.88 Example 4 97.79 95.12 77.95 Example 5 97.45 94.97 78.12 Comparative Example 1 96.54 90.58 71.55

[0091] As can be seen from Table 1, from Example 1 to Example 3, with the increase in the amount of boric acid added, on the one hand, the boron doping content increases, thereby increasing the electrical conductivity of the overall material, so it can be seen from Table 2 that its overall rate performance has been significantly improved. On the contrary, Comparative Example 1 does not have the doping of boron, so the electrical conductivity and rate performance are poor. On the other hand, with the increase in the proportion of boric acid added, the residual carbon rate also increases significantly. This is because a three-dimensional network structure containing boron is formed during the polymerization process, which significantly increases the thermal cracking temperature of the material, thereby reducing the generation of volatile carbon oxides such as CO2 during the resin curing carbonization process, thereby enhancing the stability of the carbonized layer. Introducing boron into PF can also increase the graphitization degree and crystallinity of the carbon layer, so that BPF forms a more ordered and compact carbon structure during the thermal decomposition process, reducing the defects of the carbon layer microstructure, which is beneficial for improving its residual carbon rate and material conductivity. The overall residual carbon rate of Example 4 and Example 5 is lower than that of Example 1 because, as the formaldehyde content increases, the free phenol content decreases, the polymerization crosslinking degree increases, and thus the residual carbon rate increases. However, as the formaldehyde content is too high, the free formaldehyde content increases, and the excess formaldehyde forms a large number of hydroxymethyl groups and crosslinks itself, increasing the viscosity, which is not conducive to the continued polymerization reaction. Therefore, as the formaldehyde content increases, the crosslinking degree first increases and then decreases, and the residual carbon rate also increases and then decreases. The residual carbon rate reaches the maximum when the phenol-formaldehyde ratio is 1:1.5.

[0092] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a silicon-carbon negative electrode material, comprising the following steps: a) mixing a phenol monomer, an aldehyde solution, aqueous ammonia and water, adding a boric acid solution dropwise to react, and obtaining a boron-containing phenolic resin after curing; b) carbonizing the boron-containing phenolic resin obtained in step a), mixing it with a base, and activating it to obtain boron-doped porous carbon; c) using a gaseous silicon source to deposit silicon on the boron-doped porous carbon obtained in step b), then using a gaseous carbon source to perform carbon coating, and obtaining a silicon-carbon negative electrode material after cooling.

2. The preparation method according to claim 1, characterized in that: The phenol monomer in step a) is selected from one or more of phenol, m-phenol, and boric acid phenyl ester; The aldehyde solution is selected from one or more of formaldehyde solution, acetaldehyde solution, furfural solution and paraformaldehyde solution; The phenol-aldehyde molar ratio of the phenol monomer to the aldehyde solution is 1:(1-2).

3. The preparation method according to claim 1, characterized in that: The mixing method in step a) is stirring; the stirring speed is 50r / min to 250r / min, the temperature is 50°C to 90°C, and the time is 2h to 3h.

4. The preparation method according to claim 1, characterized in that: The mass ratio of the boric acid solution added dropwise in step a) is 1% to 10%; The reaction temperature is 50° C. to 90° C., the stirring speed is 50 r / min to 250 r / min, and the stirring time is 1 h to 3 h.

5. The preparation method according to claim 1, characterized in that: The curing temperature in step a) is 100° C. to 180° C., and the curing time is 20 h to 36 h.

6. The preparation method according to claim 1, characterized in that: The carbonization process in step b) is specifically as follows: The boron-containing phenolic resin is placed in a tubular furnace, and the nitrogen flow rate is set to 0.5L / min to 2L / min for evacuation for 1h to 2h, and then the nitrogen flow rate is reduced to 0.1L / min to 0.5L / min, and the temperature is increased to 700°C to 1000°C at a heating rate of 2°C / min to 5°C / min, and carbonized for 1h to 3h. After natural cooling, boron-doped carbon is obtained.

7. The preparation method according to claim 1, characterized in that: The activation process in step b) is specifically as follows: The carbonized boron-containing phenolic resin is mixed with an alkali in an alkali-carbon ratio of 1: (1-4), placed in a nickel crucible and placed in a tubular furnace, the nitrogen flow rate is set to 0.5L / min-2L / min, emptied for 1h-3h, then the nitrogen flow rate is reduced to 0.1L / min-0.5L / min, the temperature is increased to 350℃-450℃ at a heating rate of 2℃ / min-5℃ / min, kept warm for 0.5h-2h, then heated to 700℃-900℃ at a heating rate of 5℃ / min-10℃ / min, activated for 0.5h-2h, and naturally cooled and crushed by air flow to obtain boron-doped porous carbon.

8. The preparation method according to claim 1, characterized in that: The gaseous silicon source in step c) is selected from one or more of monosilane, disilane, monochlorotrihydrosilane, dichlorosilane, trisilane, trichlorosilane and silicon chloride; The silicon deposition process is specifically as follows: The boron-doped porous carbon is placed in a rotary furnace, and the nitrogen flow rate is set to 1L / min~5L / min for 1h~3h, and the nitrogen flow rate is reduced to 0.5L / min~1L / min, and then the temperature is increased to 300℃~600℃ at a heating rate of 2℃ / min~5℃ / min, and a gaseous silicon source is introduced, and the flow rate ratio of the gaseous silicon source to nitrogen is (2~4):

1. Silicon deposition is carried out by chemical vapor deposition for 6h~10h to complete the silicon deposition process.

9. The preparation method according to claim 1, characterized in that: The gaseous carbon source in step c) is selected from one or more of acetylene, methane, ethane and ethylene; The process of carbon coating using a gaseous carbon source is specifically as follows: After silicon deposition is completed, the valve of the gaseous silicon source is closed, the nitrogen flow rate remains unchanged, and a gaseous carbon source is introduced at a flow rate of 0.5L / min to 1L / min. Vapor deposition is performed for 1h to 3h to obtain a boron-doped silicon-carbon negative electrode material.

10. A silicon-carbon negative electrode material, characterized in that: The preparation method is described in any one of claims 1 to 9.

Citation Information

Cited By

  • Silicon-carbon negative electrode material and preparation method thereof

    CN120784323A

  • Spherical resin sphere and spherical porous carbon suitable for silicon-carbon negative electrode and preparation method of spherical resin sphere and spherical porous carbon

    CN121076115A

  • A spherical resin pellet and a spherical porous carbon suitable for a silicon-carbon negative electrode and a preparation method thereof

    CN121076115B

  • Preparation method and application of silicon-carbon negative electrode material

    CN121516853A

  • Preparation method and application of silicon-carbon negative electrode material

    CN121516853B